Model Penyelesaian Kerugian Negara/Daerah Lewat Tuntutan Perbendaharaan dan Tuntutan Ganti Rugi(TP-TGR) (Studi Kasus di Kabupaten Rembang) - , Fahrudin, Prof. Dr. Absori, S.H., M.Hum, Prof. Dr. Aidul Fitriciada Azhari, S.H., M.Hum (2017)
The purpose of this research was to determine the loss settlement countries / regions through repertory demands and damages (TP-S), to determine the implementation of the Settlement loss countries / regions through treasury and Indemnity Claims (TP-S) in the District of Apex, and construct how the model Settlement loss countries / regions in the future. This type of research is the study of normative juridical approach (Juridical approach), date used secondary data (literature) consisting of primary legal materials, secondary and tertiary. The results of the study found; (1) completion of a country other than the loss pursued through the criminal and civil administrative channels are also available as an internal control both central and local bureaucracy, kerugaiannegra it could be money or goods performed by the treasurer or not bendaha as well as other parties, involving actors treasurer handled by CPC, while perpetrators carried out by civil servants not the treasurer or other officer, by a team called the Assembly of the TP-SE. (2) recovery of damages in the district Country / region conducted by the SE, while the cases only civil cases not done by the treasurer or other officer, with a variety of motifs, implementation that there is complete and there is not yet finished, unfinished because disebakakan by bebera things: a) there bebasa decision of the court which is final, b) the offender has been fired, c) the perpetrator had not been identified d) then the absence of a reference singkoronisasi rules, especially the team's technical directives vacancy norm. (3) future models need to be made to repair the existing miraculous aspects: a) institutions need to be strengthened, b) existing regulations must be made synchronous and sufficient in order to be a definitive reference TPGR teams, such as technical regulations that have not been there for a while it's recommended to make PERDA fill the kekososngan, c) for which difficult cases encountered such cases already get free pustasan of penagdilan should not be made a rule that states no longer allowed to be processed by the SE team, as it collides with the principle of legal certainty and well-laws. So it is necesssry also to do judicial review of article 6 paragraph (1) of 2004 on the state treasury.